(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2026)
The research aims to clarify the ruling on a woman praying in pants and appearing in them before non-mahram men. Its importance lies in addressing an issue that generates much debate in society, ranging from those who are excessively strict to the point of declaring the prayer of a woman in pants invalid, and condemning all who wear pants as immoral, to those who permit the matter entirely without any restrictions; as well as those who misinterpret the statements of jurists and apply them to reality. To move away from these extremes, the ruling on the issue has been clarified through a foundational jurisprudential study based on the understanding of respected jurists, away from purely admonitory discourse. This research has shown that a woman’s prayer in pants is valid, even if it restricts the ’awrah according to the consensus of the jurists of the schools of thought, provided that the skin does not show through it. Furthermore, a woman appearing in pants before non-mahram men is considered haram by the Hanafi and Maliki schools if it restricts the ’awrah in a way that leads to temptation, as they are akin to naked women; and it is deemed makruh by the Shafi’i and Hanbali schools, emphasizing modesty in its linguistic sense and prioritizing the literal meaning over the metaphorical. It is understood from the hadith about "dressed yet naked" that it refers to those whose skin color or parts of it show, not those whose ’awrah is outlined; and there is no necessary connection between the differences in the ’awrah and its limits in prayer and outside of prayer and the covering. Likewise, there is no necessary connection between the covering that restricts the ’awrah and the gaze of foreign men upon it. It is prohibited for a non-mahram, and even for a mahram, to look at her if the gaze arouses lust. This is different from when skin color appears, which is prohibited for the woman in all cases, even if there is no one looking at her. Despite this disagreement, the view of those who declare it haram aligns with the objectives of Sharia due to the corruption of the times